Of sin, gender equality and environmental goodness - towards curbing the effects of necrophilia - Mwandayi, Canisius (HTS teologiese studies, 2023)
The Old Testament connects environmental disasters with sin. The expulsion from the paradeiso (Gn 3:23–24), the plagues on Egypt (Ex 7–11) and droughts (Am 4.6; Jr 14:1–7) are all portrayed as linked with sin. Theologically, human sin, therefore, can lead to actions that have adverse effects upon humans and the environment. It is against this reality that this research explores the effects of necrophilia not only upon humans but also on the environment. The argument raised here is that while world leaders are making concerted efforts to achieve gender equality, among other goals by 2030, necrophilia is likely to offset this vision as women continue being reduced to mere sex machines in life and beyond death. Spiritually, as a result of the evil nature of necrophilia, God and the ancestors also are forced to turn their faces from a land where such abomination is practiced, hence exposing the land to environmental catastrophes. Using largely the qualitative approach as well as comparative analysis, the research engages in an informed conversation with African traditional religion (ATR), Christianity and Islam (religions that have a large following in Zimbabwe), examining to what extent they can be used to curb necrophilia.Contribution: The research makes a unique contribution to Religion and/or Theology and Constructions of Earth and Gender through raising an awareness of the high chances of necrophilia offsetting efforts to achieve gender equality by 2030. It also proffers tangible ways of curbing the harmful effects of necrophilia upon human societies and Mother Earth.